The Effect of Discipline, Commitment, and Organizational Climate on Employee Performance at the Tanjung Wangi Class III Harbor Authority and Port Authority Office - Widodo Widodo; Suwignyo Widagdo; Dedy Wijaya Kusuma (International Journal of Economics, Commerce, and Management, 2025)
Government institutions play a crucial role in providing public services, implementing state policies, and managing public administration. Human resource management in institutions aims to enhance employee productivity to support the achievement of organizational goals. This study aims to analyze the influence of discipline, commitment, and organizational climate on employee performance at the Kesyahbandaran and Port Authority Office Class III Tanjung Wangi. The research employs a quantitative approach with a causal study design. Data were collected from 90 respondents using a sampling technique and analyzed using multiple regression analysis. The results indicate that work discipline has a significant partial effect on employee performance, where higher discipline enhances productivity. Commitment has a significant partial effect, showing that employees with high loyalty and moral responsibility tend to perform optimally. A positive organizational climate significantly increases employee performance by creating a conducive work atmosphere. Simultaneously, discipline, commitment, and organizational climate significantly influence employee performance, suggesting that these three variables complement each other in enhancing work efficiency and effectiveness. The findings are expected to serve as a reference for government institutions in formulating policies and strategies to improve employee performance through discipline management, commitment reinforcement, and the establishment of a positive organizational climate.